Understanding Peri-implantitis: Cellular Mechanisms and Microbiological Analysis - Mahesh, Lanka; Shukla, Sagrika; Gulati, Nikita (British Journal of Healthcare and Medical Research, 2025)
Peri-implantitis is the one of the main reasons for a dental implant failure leading to a cascade of other oral problems to follow. The inflammatory lesions causing implant failure also make the surrounding bone to resorb, sometimes making re-implant placement impossible. This article discusses about the events that occur at the cellular and histopathological level. This article also discusses the histopathological difference between periimplantitis and periodontitis.